Global trends in international research collaboration, 1980-2021① - Aksnes Dag W.; Sivertsen Gunnar (Journal of Data and Information Science, 2023)
The aim of this study is to analyze the evolution of international research collaboration from 1980 to 2021. The study examines the main global patterns as well as those specific to individual countries, country groups, and different areas of research.